Pertumbuhan Bibit Kayu Manis (Cinnamomum burmanii Blume) pada Berbagai Kombinasi Pupuk NPK dengan Pupuk Hayati Bioneensis - Mayangsari, Serli Sapitri; Hartawan, Rudi; Hayata, Hayata (Jurnal Media Pertanian, 2025)
Cinnamon is an important commodity in Indonesia. Cinnamon harvesting is destructive, requiring seedlings to replace harvested plants. Preparing quality seedlings is one effort to increase plant productivity. The study aims to obtain the right combination of NPK compound fertilizer with Bioneensis biofertilizer to support the growth of cinnamon seedlings. The study was conducted from May to August 2024. Field research was conducted at the Rice Seed Center in Jembatan Mas Village, Pemayung District, Batanghari Regency. Plant growth analysis was conducted at the Basic Laboratory of the Faculty of Agriculture, Batanghari University. Soil chemical analysis was conducted at the BSIP Laboratory. The study used a completely randomized environmental design and a treatment design in the form of a combination of NPK fertilizer with Bioneensis biofertilizer (k) as follows; k0: control, k1: 100% NPK, k2: 100% Bioneensis, k3: 75% NPK + 25% Bioneensis, k4: 50% NPK + 50% Bioneensis, k5: 25% NPK + 75% Bioneensis. The parameters observed were chemical and physical analysis of the soil, plant height, stem diameter, total dry weight, shoot root ratio, water content of the planting medium and seedling quality index. The soil analysis data were tabulated and the plant growth observation data were analyzed for variance and continued with the Duncan test at the α level of 5%. The results showed that the treatment did not change the soil fertility status except for phosphorus content. The treatment significantly affected the seedling growth parameters. The results showed that the k5 treatment (25% NPK fertilizer (dose 2.5 g) + 75% Bioneensis (dose 4.68 g)) increased seedling height by 31.18%; stem diameter by 22.50%; total dry weight by 91.68%; and quality index by 70%. The k5 treatment decreased the shoot root ratio by 20.09%. Bioneensis fertilizer can substitute NPK fertilizer by 75%.